Central Nervous System Tumors - George Turner, Scott (IntechOpen, 2022)
Though the treatment of central nervous system (CNS) tumors has been challenging, new advances have helped us better understand the molecular and genetic makeup of many tumor types, and new chemotherapies and immunotherapies have extended survival in patients with aggressive primary CNS tumors. This book discusses pediatric and adult tumors of the CNS, the classification schemes used to categorize them, advances in surgical techniques, and several important genetic alterations found in these tumors. We hope this book contributes to the reader's understanding of these tumors and provides the most up-to-date and cutting-edge discoveries in this exciting field.